2012
DOI: 10.4014/jmb.1107.07021
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Bacillus sp. Producing Broad-Spectrum Antibiotics Against Human and Plant Pathogenic Fungi

Abstract: A strain of bacterium producing antifungal antibiotic was isolated and identification of the strain was attempted. We could identify the bacterium as being a Bacillus sp., based on morphological observation, physiological characteristics, and 16S rDNA sequence analysis, thus leading us to designate the strain as Bacillus sp. AH-E-1. The strain showed potent antibiotic activity against phytopathogenic and human pathogenic fungi by inducing mycelial distortion and swelling and inhibiting spore germination. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
5
2
0
Order By: Relevance
“…Previous studies have shown that B. amyloliquefaciens strains possess significant antifungal activity against F. oxysporum , which suppresses Fusarium wilt in various crops, such as watermelon and tomato [ 50 , 52 , 53 , 54 , 55 , 56 , 57 ]. Moreover, the cell-free supernatant of the B. amyloliquefaciens DHA55 culture displayed significant growth-inhibiting potential against different pathogenic fungi, including Fon , Db , Fg , Ss , and Rs ( Figure 7 ), similar to observations that cell-free supernatants of B. subtilis and B. amyloliquefaciens inhibited the mycelial growth and/or spore germination of Macrophomina phaseolina , the causal agent of charcoal rot in soybean and common bean, and Fusarium semitectum , which causes rice dirty panicle disease, respectively [ 58 , 59 , 60 ]. Moreover, lipopeptide extract of B. amyloliquefaciens DHA55 at 100 µg/mL significantly inhibited Fon growth ( Figure 7 C), which was consistent with previous observations regarding B. methyltrophicus TEB1 and B. amyloliquefaciens SYBC H47 [ 49 , 61 , 62 , 63 ].…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies have shown that B. amyloliquefaciens strains possess significant antifungal activity against F. oxysporum , which suppresses Fusarium wilt in various crops, such as watermelon and tomato [ 50 , 52 , 53 , 54 , 55 , 56 , 57 ]. Moreover, the cell-free supernatant of the B. amyloliquefaciens DHA55 culture displayed significant growth-inhibiting potential against different pathogenic fungi, including Fon , Db , Fg , Ss , and Rs ( Figure 7 ), similar to observations that cell-free supernatants of B. subtilis and B. amyloliquefaciens inhibited the mycelial growth and/or spore germination of Macrophomina phaseolina , the causal agent of charcoal rot in soybean and common bean, and Fusarium semitectum , which causes rice dirty panicle disease, respectively [ 58 , 59 , 60 ]. Moreover, lipopeptide extract of B. amyloliquefaciens DHA55 at 100 µg/mL significantly inhibited Fon growth ( Figure 7 C), which was consistent with previous observations regarding B. methyltrophicus TEB1 and B. amyloliquefaciens SYBC H47 [ 49 , 61 , 62 , 63 ].…”
Section: Discussionsupporting
confidence: 76%
“…The structures of the compounds were then confirmed using 1 H NMR ( Figures S1 {Supplement 1} through S5 {Supplement 5}). All of the isolated compounds were small cyclic peptides ( Figure 6); the characterization data for each compound were in good agreement with the literature (Chen et al, 2009;Nakamura et al, 2006;Stark and Hofmann, 2005). 195.1128195.…”
Section: Purification and Identification Of Antifungal Metabolitessupporting
confidence: 86%
“…The absence of a germination tube emerging from the surface of conidia indicated that bacterial compounds completely inhibited the spore germination in P. verrucosum, A. westerdijikae and F. oxysporum. These findings are in line with earlier studies [30,31], reporting similar spore germination inhibition by bacterial antifungal compounds. The ability of the QBC03 antagonistic compounds to maintain their antifungal activity, even after boiling for 30 min, is the most promising feature for their possible application in future.…”
Section: Discussionsupporting
confidence: 93%